A comparison the effectiveness of wholebody vibration, progressive resistive exercise and home-based exercise in patients with knee osteoarthritis - Pekesen Kurtça, Mine; Baş Aslan, Ümmühan; Kuyucu, Ersin (BMJ Publishing Group, 2017)
[Abstract Not Available]
Keywords: Wholebody Vibration; Osteoarthritis; Resistive Exercise